2022
DOI: 10.3389/fonc.2022.868411
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model for Prognosis and Therapeutic Response in Hepatocellular Carcinoma Based on a Panel of Three MED8-Related Immunomodulators

Abstract: The current tumor-node-metastasis (TNM) system is limited in predicting the survival and guiding the treatment of hepatocellular carcinoma (HCC) patients since the TNM system only focuses on the anatomical factors, regardless of the intratumoral molecule heterogeneity. Besides, the landscape of intratumoral immune genes has emerged as a prognostic indicator. The mediator complex subunit 8 (MED8) is a major polymerase regulator and has been described as an oncogene in renal cell carcinoma, but its pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The molecular subgroups can only be detected from patients' transcriptomes which, in turn, map to distinctive clinical phenotypes through consensus clustering 11 . Increasing studies demonstrate that the heterogeneity of disease molecules influences local cell function, clinical outcomes and therapy response 22,23 . For example, in an analysis of lower‐grade glioma samples, three immune subgroups were found to have different genetic alterations and lymphocyte signatures 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular subgroups can only be detected from patients' transcriptomes which, in turn, map to distinctive clinical phenotypes through consensus clustering 11 . Increasing studies demonstrate that the heterogeneity of disease molecules influences local cell function, clinical outcomes and therapy response 22,23 . For example, in an analysis of lower‐grade glioma samples, three immune subgroups were found to have different genetic alterations and lymphocyte signatures 24 .…”
Section: Discussionmentioning
confidence: 99%
“… 11 Increasing studies demonstrate that the heterogeneity of disease molecules influences local cell function, clinical outcomes and therapy response. 22 , 23 For example, in an analysis of lower‐grade glioma samples, three immune subgroups were found to have different genetic alterations and lymphocyte signatures. 24 Additionally, an exploration was performed into the classification of AMI based on early‐warning biomarker profiling to facilitate better stratification of patients with AMI responsive to clinical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation plays an important role in maintaining intestinal integrity and barrier function [ 7 ]. The PCNA is considered to be a marker of cell proliferation in various tissues [ 9 ]. Shao et al [ 10 ] and Kang et al [ 37 ] reported that Zn could increase the number of PCNA-positive cells in the Caco-2 cells or mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cell proliferation is crucial for preserving the integrity and function of the small intestine [ 8 ]. The number of proliferating cell nuclear antigen (PCNA)-positive cells is considered to be a biomarker of cell proliferation in various tissues [ 9 ]. Shao et al [ 10 ] reported that Zn deficiency decreased PCNA-positive cells in the Caco-2 cells of mice.…”
Section: Introductionmentioning
confidence: 99%
“…The level of MED8 expression was observed to be elevated in HCC tissues. The suppression of MED8 led to a notable decrease in the proliferation and migration of HepG2 and Huh7 cells [ 83 ]. Further investigation has elucidated that MED8 plays a crucial role in determining a poor prognosis in HCC, principally by promoting cancer progression through the activation of TH2 cytokines [ 84 ].…”
Section: Discussionmentioning
confidence: 99%